Historical Study in the U.S.: Assessing the impact of Tuning within a professional disciplinary society - Daniel J. McInerney (Universidad de Deusto, 2018)
The U.S.-based American Historical Association (AHA), the largest - and most influential - professional organization for historians, was the first disciplinary society in the world to lead a Tuning project, launching its work in 2012. This essay analyzes a survey distributed to historians on campuses that have taken part in the AHA Tuning project. The purpose is to understand, after six years of work on the project, what practical difference Tuning has made for historians, students, courses, curricula, and departments. Survey data indicate that, under the disciplinary society's guidance and encouragement, historians have created meaningful learning outcomes, implemented the objectives in courses and curricula, and begun work in the measurement of student learning. Not surprisingly, the project has faced limits and obstacles, particularly with leadership of the work, faculty buy-in, administrative support, follow-up assistance, enrollment concerns, student engagement, and outreach to stakeholders. However, after half a dozen years of activity, U.S. historians have made marked progress not only in articulating disciplinary learning outcomes (as have colleagues in other parts of the world) but also in implementing and assessing those objectives. While precise readings of "impact" remain elusive, a Tuning project under the direction of a disciplinary society has helped generate significant pedagogical, curricular, and cultural changes in the field of history.. Received: 03 April 2018 Accepted: 12 November 2018 Published online: 29 November 2018